Adherence to antidiabetic therapy: a concept analysis - Mukona, Doreen; Dzimiri, Tafara; Chauke, Lilian; Ndaimani, Augustine; Zvinavashe, Mathilda (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Many diabetic patients do not adhere to their medication regimen. This may be due to patientsand healthcare staff having different understanding on what constitutes adherence to antidiabetictherapy. Consequently patients and healthcare staff have not been able to achieve the desiredhealth outcomes.ObjectivesThe aim of this concept analysis is to clarify and define the concept of adherence to antidiabetictherapy. This analysis will provide a common basis for those pursuing a better understanding ofpatient decision making, reduction of complications and improved long-term adherence toantidiabetic therapy.MethodsA concept analysis, utilizing the eight steps Walker and Avant method was done. Eleven articleswere reviewed to produce a definition of adherence to antidiabetic therapy.ResultsAttributes of adherence to antidiabetic therapy includes knowledge of optimal level of bloodglucose and home blood glucose monitoring, knowledge of complications from poor glycaemiccontrol, use of daily medication reminders, knowing and agreeing to the medication, activecontinuous collaboration between patient and health care provider in communicating andnegotiating the treatment regimen, and ability to meet outcome targetsConclusionAdherence to antidiabetic therapy is defined as knowing and agreeing to antidiabetic therapy(medication, diet and exercises), active continuous patient participation in negotiation andappraisal of therapy, and consistence in performing desired health behaviours to meet outcometargets. The concept analysis will assist health professionals in standardising treatment guidelineswhich enables them to continually measure and improve adherence to antidiabetic therapy.